1993
DOI: 10.1007/bf01212935
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal constitution of mouse blastocysts derived from oocytes inseminated by multiple sperm insertion into the perivitelline space

Abstract: Mosaicism and parthenogenesis appear to be increased significantly following microinjection of multiple spermatozoa under the zona pellucida of mouse oocytes, and there was no evidence of aneuploidy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Postzygotic diploidization of triploids was also described by Grossmann et al who reported a significant proportion (36%) of 3PN ICSIderived zygotes that were actually diploid with respect to chromosome number [32]. These results are also consistent with Macas et al [23] who reported a 32% incidence of postzygotic diploidization of triploids. Postzygotic diploidization of triploids may arise from the abnormal distribution of the maternal chromosomes into two separate sets after extrusion of the first PB [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Postzygotic diploidization of triploids was also described by Grossmann et al who reported a significant proportion (36%) of 3PN ICSIderived zygotes that were actually diploid with respect to chromosome number [32]. These results are also consistent with Macas et al [23] who reported a 32% incidence of postzygotic diploidization of triploids. Postzygotic diploidization of triploids may arise from the abnormal distribution of the maternal chromosomes into two separate sets after extrusion of the first PB [32].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the early cleavage divisions in human and mouse embryos have been shown to be error-prone and could contribute to the formation of mosaic embryos [19]. Studies also suggest that 2n/4n mosaicism is a normal feature of the later-stage embryos and that there is a nonrandom allocation of the tetraploid cells within the embryo [17,[20][21][22][23]. Ruangvutilert et al [17] described the presence of tetraploid cells in a significant proportion of arrested cleavage-stage human embryos (6/20) and at an even higher proportion of human blastocyst stage embryos (14/19).…”
Section: Discussionmentioning
confidence: 96%
“…Haploidy has been observed in the embryos of domestic animals and humans with frequencies of 1% to 22%. The highest percentage of haploidy reported until now -22% -was observed by Macas et al (1993) when analysing mouse blastocysts from oocytes inseminated by multiple injection in the perivitelline space. In 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 Cytogenetic analysis of caprine embryos produced in vitro 197 pigs, haploid embryos accounted for 12.2% of embryos (Underhill et al, 1991), in sheep, 2.7% (Murray et al, 1985) and in human embryos, 2.6% (Jamiesson et al, 1994) and 11.8% (Pellestor et al, 1994b).…”
Section: Discussionmentioning
confidence: 95%
“…See text for details. polar body and the two pronuclei was checked for every zygote to ensure normal fertilization and to exclude parthenogenetic activation of oocytes (Macas et al, 1993). The zygotes were then cultured (in Ham F 10 medium with 10 per cent human foetal cord serum at 37°C and 5 per cent CO2 in air) until they reached the blastula stage.…”
Section: Methodsmentioning
confidence: 99%